PEMANFAATAN WEBLOG SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS - Tina Mariany Kariman; Eddy Mulia (Jurnal Teknologi Pendidikan (JTP), 2012)
Instructional Media is one of important aspects in learning process. Intructional media is used to make learning process easier. One of instructiona media in learning process is weblog. Weblog is an instructional media based on internet. Weblog is more efficient and effective in learning process. It can be accessed everytime. Students will be active in learning because the students have to find out their materals in the weblog